Production of Cost-Effective Adsorbents from Native Materials - Nwufo, Bethrand Tabugbo; Priscila, Attah U; Onche, Emmanuel Usman (International Journal of Chemistry and Materials Research, 2014)
The adsorption of methyl red by activated carbon produced from five native materials: Ram horn, plantain peels, Sugar cane chaff, Car tyre and Ram hair were studied invivo. Methyl orange was significantly adsorbed by all the activated carbons and the rate increased with time until equilibrium was reached after 24 h. The Freundlich’s adsorption parameters were determined to be 1.71 (plantain peel), 1.20 (car tyre), 1.14 (ram hair), 1.02 (sugar cane chaff) and 1.00 (ram horn). In this study, plantain peel has the highest adsorptive capacity while ram horn has the least. The order of adsorptive capacity is plantain peel>car tyre>ram hair>sugar cane chaff>ram horn. The use of these native materials as adsorbents will lead to cost efficiency and reduce operational cost.